Kabit: Eskandalo sa Panahon ng Eleksyon - Javier, T.L (Likhaan: The Journal of Contemporary Philippine Literature, 2024)
This poem was forged during the 2022 campaign season. It follows the tale of two siblings who faced the wrath of their family and neighbors because of a scandalous scenario.